A feasibility study of establishing Khryssleen's Seafood Restaurant in Samonte Park, PN, Cavite City - Reus, Kristine Anne E., author; Laguardia, Mylene P., author; Evangelista, Fedelita R., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2003)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2003.
Includes bibliographical references and appendices.
Keywords: Variety of sea foods; Take-out service; Dine-in service; Feasibility study; Seafood delights; Affordable prices; Traditional recipes